Characterizing functional alterations in instrumental activities of daily living using latent class analysis: a population-based study (NEDICES). (2nd January 2020) - Contador, Israel; Fernández-Calvo, Bernardino; Rueda-Revé, Laura; Olazarán, Javier; Bermejo-Pareja, Félix
Abstract: Background and Objectives: The existence of different patterns of functional impairment in older adults has scarcely been addressed. This research investigates major patterns of functional impairment based on Pfeffer's Functional Activity Questionnaire (FAQ). Research Design and Methods: The participants come from NEDICES (Neurological Disorders in Central Spain), a prospective population-based cohort study. A total of 3837 individuals without dementia who completed the Spanish version of the FAQ was selected. Latent Class Analysis (LCA) was carried out to examine potential cluster subgroups based on FAQ responses. Results: The FAQ showed good internal consistency (Cronbach's alpha: 0.86) and moderate correlation (r = −.40) with cognitive performance on the Mini-Mental State Examination (MMSE-37). The response patterns revealed the presence of three latent classes: absence of functional alteration (Class 1), established functional alteration (Class 2), and minimal functional alteration (Class 3). Moreover, the probability of resolving Items 2 ('shopping alone for…'), 3 ('heating water…'), 4 ('preparing a balanced meal'), and 9 ('travelling out of neighbourhood…') was close to 0% for Class 2 membership, while those with the lowest probability of resolution for Class 3 were Items 2 and 9. Items 3 and 4 were the best to discriminate between different grades of functional alterations (Class 2 vs. Class 3). Discussion and Implications: Our findings indicate that the combination of overall FAQ score and item response pattern may help to classify individuals with different subtypes of functional impairment. The Spanish version of the FAQ is a useful tool for detection of functional impairment in older adults.